Building a Professional Identity and an Academic Career Track in Translational Medicine - van Dijk, Sabine J.; Domenighetti, Andrea A.; Gomez-Ospina, Natalia; Hunter, Patricia; Lindemans, Caroline A.; Melotte, Veerle; van Rossum, Annemarie M. C.; Rosenblum, Norman D. (Frontiers in Medicine, 2019)
Biomedical scientists aim to contribute to further understanding of disease pathogenesis and to develop new diagnostic and therapeutic tools that relieve disease burden. Yet the majority of biomedical scientists do not develop their academic career or professional identity as “translational scientists”, and are not actively involved in the continuum from scientific concept to development of new strategies that change medical practice. The collaborative nature of translational medicine and the lengthy process of bringing innovative findings from bench to bedside conflict with established pathways of building a career in academia. This collaborative approach also poses a problem for evaluating individual contributions and progress. The traditional evaluation of scientific success measured by the impact and number of publications and grants scientists achieve is inadequate when the product is a team effort that may take decades to complete. Further, where scientists are trained to be independent thinkers and to establish unique scientific niches, translational medicine depends on combining individual insights and strengths for the greater good. Training programs that are specifically geared to prepare scientists for a career in translational medicine are not widespread. In addition, the legal, regulatory, scientific and clinical infrastructure and support required for translational research is often underdeveloped in academic institutions and funding organizations, further discouraging the development and success of translational scientists in the academic setting. In this perspective we discuss challenges and potential solutions that could allow for physicians, physician scientists and basic scientists to develop a professional identity and a fruitful career in translational medicine.